1999
DOI: 10.1097/00007890-199906270-00020
|View full text |Cite
|
Sign up to set email alerts
|

ANGIOGENESIS IN THE huPBL-SCID MODEL OF HUMAN TRANSPLANT REJECTION1

Abstract: A significant angiogenesis response was associated with the cell infiltrates in the human skin allografts. The onset of angiogenesis appeared after the initial development of localized infiltrates and preceded the development of microvascular destruction. These findings suggest that alloreactive T cells and/or monocytes mediate the angiogenesis response in skin allografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 15 publications
6
44
0
Order By: Relevance
“…However, the association of inflammatory cell infiltration with angiogenesis has been established. The angiogenesis process is known to be proinflammatory due to enhanced adhesion and permeability in inflammatory lesions (21). We also found that von Willebrand factor was expressed diffusely and more intensely on large vessels as well as small vessels in affected lesions than in non-affected areas.…”
Section: Discussionsupporting
confidence: 55%
“…However, the association of inflammatory cell infiltration with angiogenesis has been established. The angiogenesis process is known to be proinflammatory due to enhanced adhesion and permeability in inflammatory lesions (21). We also found that von Willebrand factor was expressed diffusely and more intensely on large vessels as well as small vessels in affected lesions than in non-affected areas.…”
Section: Discussionsupporting
confidence: 55%
“…Full-thickness human neonatal foreskin grafts were transplanted onto CB.17 SCID mice as described (4,36) and were allowed to heal for 4-6 weeks. For humanization, peripheral blood lymphocytes (PBLs) were isolated from leukapheresis packs obtained from the Blood Donor Centers at the Children's Hospital and the Dana Farber Cancer Institute (Boston, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Frozen specimens were fixed in acetone, and formalin-fixed specimens were deparaffined. Immunohistochemistry was performed with primary and secondary horseradish peroxidase-conjugated antibodies on frozen sections as described (4,12) and on paraffin-embedded sections using the VectaStain Kit (Vector, Burlinghame, California, USA) and the Tyramide Signal Amplification (TSA) Biotin system (NEN Life Science Products, Boston, Massachusetts, USA) according to the manufacturers' instructions. All specimens were developed in 3-amino ethylcarbazole (4,12) and were counterstained in Gill's hematoxylin.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations